Umiejętność zarządzania różnorodnością kulturową - odniesienie teoretyczno-praktyczne - Stańczyk, Sylwia (Multicultural management skills - theoretical and practical approach, 2007)
This article aims to indicate a package of values that distinguish organizations successfully solving difficulties in cultural differential in contrast to many others. Such goal was achieved through analyzing discrepancies between the theory of intercultural communication and the experience coming from practice. Conclusions and hypotheses presented in the paper are based on literature studies results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 133-141